The Transcription Factor Creb is Involved in Sorafenib-Inhibited Renal Cancer Cell Proliferation, Migration and Invasion - Huang Shuaishuai; Cui Pinger; Lin Shuangxia; Yao Xuping; Wang Xue; Ren Yu; Weng Guobin (Acta Pharmaceutica)
Our previous reports showed that the cyclic-AMP-response element-binding protein (CREB) served as a proto-oncogene in the process of tumorigenesis and mediated the growth and metastatic activity of renal cancer cells. Our study, therefore, explored the role of CREB in sorafenib- -inhibited cell proliferation, migration and invasion. Renal cancer cells were cultured in medium containing sorafenib for 12, 24, 48 and 72 h. The MTT assay was used to study the cytotoxic effects of sorafenib. Cell invasion and migration were assayed in wound healing and transwell experiments, respectively. Protein expression levels were evaluated by western blotting. The results show that sorafenib treatment decreased cell viability in a dose- and time-dependent manner. Sorafenib inhibited cell migration and invasion and decreased the expression of MMP-2 and MMP-9. Moreover, addition of the recombinant plasmid pCI-neo/ CREB (PN) reversed the sorafenib-induced inhibition of cell proliferation, migration and invasion. These results show that CREB is associated with the sorafenib-induced inhibition of proliferation, migration and invasion.